2018
DOI: 10.1142/s021812741850013x
|View full text |Cite
|
Sign up to set email alerts
|

Infinite Number of Hidden Attractors in Memristor-Based Autonomous Duffing Oscillator

Abstract: In this paper, the recent and emerging phenomenon of hidden oscillations is observed in a newly implemented memristor-based autonomous Duffing oscillator for the first time. The hidden oscillations are presented and quantified by various statistical measures. The system shows a large number of hidden attractors for a wide range of the system parameters. This study indicates that hidden oscillations can exist not only in piecewise-linear but also in smooth nonlinear circuits and systems. The distribution of Lya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…This means that the model is always stable in the x 4 direction. This kind of equilibrium gives the 'periodic line invariant' type of stability of the model, and the model is always stable for the x 4 line [54]. We evaluate the above matrix with two different sides of variable x 4 .…”
Section: System Stability Analysismentioning
confidence: 99%
“…This means that the model is always stable in the x 4 direction. This kind of equilibrium gives the 'periodic line invariant' type of stability of the model, and the model is always stable for the x 4 line [54]. We evaluate the above matrix with two different sides of variable x 4 .…”
Section: System Stability Analysismentioning
confidence: 99%
“…Some hidden chaotic systems also have the characteristic of multistability, which is reported by many scholars [50]- [52]. Vaibhav Varshney and S. Sabarathinam et al found the hidden behavior due to 'periodic line invariant' and analyzed the causes of multistable state in the reference [53]. Since the initial value is one of the key factors that affect the state of memristor, the sensitivity of the memristive chaotic system includes the sensitivity to the initial value of the memristor itself.…”
Section: Introductionmentioning
confidence: 98%
“…Several contributions make it clear that circuits containing memelements are able to display a rich variety of multistability phenomena [Li et al, 2014;Scarabello & Messias, 2014;Messias et al, 2010;Bao et al, 2016;Yuan et al, 2016a;Yuan et al, 2016b;Xu et al, 2017;Rajagopal et al, 2018;Varshney et al, 2018;Corinto et al, 2019;Yuan et al, 2019;Wang et al, 2019;Chang et al, 2019;Chen et al, 2020;Zhang et al, 2019]. To this respect, it is worth noting that multistability control is a field of general growing interest (see, e.g.…”
Section: Introductionmentioning
confidence: 99%